ANALISIS PENINGKATAN KINERJA PADA PELABUHAN CIWANDAN - BANTEN - Wulan Suciati, (2023)
Ciwandan Port is one of the international ports in Banten Province which is under the management of PT Pelabuhan Indonesia (Persero) or Pelindo. Currently, Ciwandan Port has implemented the International Ships and Port Facility Security (ISPS Code) system which makes Ciwandan Port receive many ship visits both domestically and abroad. With so many domestic and foreign ship visits, it is necessary to increase performance at Ciwandan Port for ship services and also goods services. This study aims to analyze ship visits and the flow of goods and commodities, as well as operational performance at Ciwandan Port from 2018 to 2022, and make forecasts for the next five years (2023 to 2027). This forecasting used SPSS 26 software with a linear regression method. The results of this study indicate that the total number of ship visits from 2018 to 2022 is mostly dominated by tugboats & barges, while the flow of goods is dominated by dry bulk (tons) and general cargo (m3). At the berth occupancy ratio (BOR) an average of 45.37% is found, which is still below the wharf usage level for Ciwandan Port. Forecasting results on total ship visits are expected to decrease along with the flow of goods. So that with this decrease, it is necessary to increase efforts to increase ship and goods visits, as well as approach industries in the hinterland area of Ciwandan Port.